Penerapan pendekatan RME (realistic mathematics education) untuk meningkatkan hasil belajar siswa kelas VII MTs Al-Hikmah Bululawang materi perbandingan senilai dan berbalik nilai - Siti Nur Asia; Slamet Slamet (Universitas Negeri Malang, 2021)
This study aims to describe the steps to implement the application of RME (Realistic Mathematics Education) to improve the learning outcomes of class VII students of MTs Al-Hikmah Bululawang on the subject to support and change values. This type of research is Classroom Action Research (CAR). The data collected in this study include: 1) the results of observations of teacher activities and student activities, 2) results of field notes, 3) results of the final cycle test. RME is carried out by the following steps: 1) solving contextual problems, 2) resolving contextual problems, 3) comparing and discussing answers, and 4) comparing the learning outcomes of class VII students of MTs Al-Hikmah Bululawang on approved and changed values. This increase was discussed based on the final test results of students who achieved KKM Increasing the increase by 20 percent from before the implementation of RME and 23 percent from cycle 1 to cycle 2 and supported by the level of delay in the learning process seen from the results of